Coming of Age: German Foreign Policy since 1945 - Haftendorn, Helga (Rowman & Littlefield Publishers, 2006)
In this authoritative book, the only work to cover the full sweep of German foreign policy since the end of World War II, noted scholar Helga Haftendorn explores Germany's remarkable recovery from wartime defeat and destruction. Offspring of the Cold War, the Federal Republic of Germany and the German Democratic Republic entered the international arena in 1949 under three crippling constraints: they were held accountable for the crimes of the Third Reich, they were fully dependent on the occupation powers, and their international room for maneuver was limited by an East-West conflict that placed Bonn and East Berlin on opposite sides of the Iron Curtain. Tracing the FRG's strategy of multilateralism, Haftendorn convincingly demonstrates how these liabilities transformed into opportunities as Germany found a security guarantee in NATO membership and economic and political rewards in the system of European integration. The author's overview of past half-century shows a high degree of continuity and consistency in German foreign policy despite the tumultuous events of the era. However, Haftendorn argues that Germany's traditional policy of self-restraint was increasingly counterbalanced by a more assertive stance after reunification and the rise of a post-war generation to power. Although the country's leaders continued to value international institutions, the benefits were increasingly weighed against Germany's enlightened self-interest. Scholars and students of contemporary Germany, Europe, and East-West relations will find this nuanced and knowledgeable study invaluable.